Strategi Meningkatkan Penjualan dengan Bauran Komunikasi Pemasaran pada UMKM Konveksi Sampean Kaos Kaki di Megamendung Kabupaten Bogor Jawa Barat - Dhimas Alwi Abrori; Agung Tri Putranto (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Teknologi Nusantara, 2026)
This study analyzes sales improvement strategies through the marketing communication mix at Sampean Kaos Kaki, a sock convection micro, small, and medium enterprise in Megamendung, Bogor Regency. This research applied a qualitative approach with a descriptive design. Data were collected through observation, structured interviews with five key informants, and documentation, then analyzed through data reduction, data display, conclusion drawing, Internal Factor Analysis Summary, External Factor Analysis Summary, SWOT, Internal–External Matrix, and Quantitative Strategic Planning Matrix. The findings show that sales improvement was achieved through digital promotion, discounts, bundling, customer rewards, responsive service, price variation, and direct communication through social media, marketplaces, and WhatsApp. The business has implemented eight elements of the marketing communication mix, although paid advertising, customer database management, and market segmentation remain underdeveloped. The strategic analysis indicates that the priority strategy is stabilizing production and distribution through local partnerships and operational efficiency before expanding promotional activities more aggressively.